Spectroscopic Studies of 1,10-Phenanthroline-5,6-[4,4?-(ethane-1,2-diilbis(oxy))dibenzenamine] and its Transition Metal Complexes - Serbetci, Z.; Alkan, C. (Asian Journal of Chemistry, 2010)
1,10-Phenanthroline-5,6-[4,4'-(ethane-1,2-diilbis(oxy))dibenzenamine] ligand (L) and It yields different complexes with Co(II), Ni(II), Cu(II), Cd(II) and Zn(II) acetates. The structure of the complexes and ligand determined by using elemental analysis, UV, IR, NMR, TGA. DTA, magnetic measurements.
Keywords: 1,10-Phenanthroline; Spectroscopic studies